2022
DOI: 10.1371/journal.pone.0266617
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to multidisciplinary care in a prospective chronic kidney disease cohort is associated with better outcomes

Abstract: Introduction The Renal Healthcare Program Uruguay (NRHP-UY) is a national, multidisciplinary program that provides care to chronic kidney disease (CKD) patients. In this study, we report the global results of CKD patient outcomes and a comparison between those treated at the NRHP-UY Units, with those patients who were initially included in the program but did not adhere to follow up. Methods A cohort of not-on dialysis CKD patients included prospectively in the NRHP-UY between October 1st 2004 and September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 72 publications
(70 reference statements)
0
6
0
1
Order By: Relevance
“…Covariates used for PS calculation were sex, age, number of hospital beds, index eGFR, duration of diabetes, medications, and procedures. Other covariates were not used because of missing values, and we believe that the covariates used were sufficient to adjust for confounding factors based on previous studies [ 18 , 32 34 ]. We used 1:5 matching, a logistic regression model, and the non-replacement nearest-neighbor method with a caliper width of 0.2 of the SD.…”
Section: Methodsmentioning
confidence: 99%
“…Covariates used for PS calculation were sex, age, number of hospital beds, index eGFR, duration of diabetes, medications, and procedures. Other covariates were not used because of missing values, and we believe that the covariates used were sufficient to adjust for confounding factors based on previous studies [ 18 , 32 34 ]. We used 1:5 matching, a logistic regression model, and the non-replacement nearest-neighbor method with a caliper width of 0.2 of the SD.…”
Section: Methodsmentioning
confidence: 99%
“…Patients are often managed by multiple specialists, leading to fragmentation of care, lack of holistic oversight and diffusion of responsibility for treatment. Multidisciplinary care improved transition to kidney replacement therapy and lowered mortality in single and combined outcomes analyses (Rios et al, 2022). Novel models of ‘combined clinics’ with on‐site collaboration and coparticipation (nephrologist–cardiologist–endocrinologist) may prove to be of substantial benefit for patients, in terms of reduced fragmentation of care, logistics and cost saving.…”
Section: Closing the ‘Gap’ Between What We Know And What We Domentioning
confidence: 99%
“…Policies enable rational utilization of resources, guide funding for infrastructure development, and allocation of services for optimal utilization and maximal benefit of end-users. Indeed, success of a national CKD policy has been observed in Uruguay where, since incorporation of screening for CKD in high-risk populations (case finding) into mandatory health checkups of the working population in 2009 quality of care has improved, with patients being better prepared for KRT (e.g., 44.2% vs. 21.2% having an arteriovenous fistula at the start of dialysis) and mortality among people with CKD has decreased (6.74-4.92 deaths/100 patient years) [65,66]. The ISN-Global Kidney Health Atlas (GKHA) survey found that under half of the 160 participant countries (47%) had a national NCD strategy [67].…”
Section: Health Policymentioning
confidence: 99%